The Constitutional Issue of Issuing Regulations in Iraq in Light of the 2005 Constitution An Analytical Comparative Study - Saeed, Asst.Prof.Dr. Hawraman Mohamed Saeed; Abdullah, Dr. Yahya Jalal (Sulaimani Journal for Humanities, 2025)
This research examines the administrative systems in France, Egypt, Lebanon, and Iraq, their definition, the difference between them and the law, the restrictions imposed on issuing thesesystems, an explanation of how they are issued, and determining the authority competent to issuethem in these countries. It also explains the similarity of these systems with the law, explains the difference between them, defines their types, and the circumstances and facts in which they areissued, defines the constitutional basis for issuing these various systems, identifies the legal andjudicial restrictions thatapply to the authority to issue regulations in general, and explains how todeal with issuing them of all types, In Iraq in light of the issuance of the Iraqi Constitution of 2005,and the difference between it and the constitutions that preceded its issuance:
Keywords: Systems; executive authority; restrictions; acquired rights